Agricultural bureau. Deptment of agriculture and commerce, Tokyo (Tokyo, 1910)
This book introduces about condition of agriculture, agricultural products, agricultural administration, formosa and karafuto.
Keywords: Agriculture,Nông nghiệp; Japan,Nhật Bản